The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4274/jcrpe.5020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ZnT8 Antibody in Turkish Children and Adolescents with New Onset Type 1 Diabetes

Abstract: Objective:Zinc transporter 8 protein (ZnT8A) is a transmembrane protein which functions to transfer zinc to insulin vesicles. Antibodies formed against ZnT8A (ZnT8A) are regarded as an independent autoimmunity demonstrator in type 1 diabetes (T1D). The aim of this study was to investigate the prevalence of ZnT8A in Turkish children with new onset T1D.Method:Eighty four patients between 1-18 years of age diagnosed with T1D between February 2015-March 2016 and the control group consisting of 50 healthy children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…ZnT8A assay was introduced later than the other autoantibody assays, and there are no earlier reports on a possible sex difference in the frequencies or levels of ZnT8A at the time of diagnosis. 41,42 To our knowledge, this is the first study reporting significant sex differences in the frequencies of IAA, IA-2A, and ZnT8A in children with T1D after adjustment for age at diagnosis. GADA frequencies have been observed repeatedly to be higher in female than in male patients and in older children than in young children.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…ZnT8A assay was introduced later than the other autoantibody assays, and there are no earlier reports on a possible sex difference in the frequencies or levels of ZnT8A at the time of diagnosis. 41,42 To our knowledge, this is the first study reporting significant sex differences in the frequencies of IAA, IA-2A, and ZnT8A in children with T1D after adjustment for age at diagnosis. GADA frequencies have been observed repeatedly to be higher in female than in male patients and in older children than in young children.…”
Section: Discussionmentioning
confidence: 75%
“…A study by Williams et al on the IAA prevalence at diagnosis of T1D in children and adolescents showed a higher prevalence in males but only in those aged 15 to 20 years. The ZnT8A assay was introduced later than the other autoantibody assays, and there are no earlier reports on a possible sex difference in the frequencies or levels of ZnT8A at the time of diagnosis . To our knowledge, this is the first study reporting significant sex differences in the frequencies of IAA, IA‐2A, and ZnT8A in children with T1D after adjustment for age at diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…ZnT8 is a six-transmembrane protein transporter and a member of the cation diffusion family that facilitates the transport of Zn +2 ions from the cytoplasm to insulin vesicles [8,9]. It plays an essential role in the storage, secretion, structural stabilization, and action of insulin [10,11]. Frequent exposure of ZnT8 antigen occurs during the exocytosis of insulin that is stimulated by glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Once ZnT8 is exposed, it can trigger or exacerbate the ZnT8A (ZnT8 autoantibodies) in genetically susceptible individuals (7). Previous studies have reported autoantibodies to ZnT8 is highly prevalent among T1D children with new onset, and it could be a marker for disease risk (8,9,10,11). The cation efflux transporter ZnT8 may influence the development of ZnT8 immunogenicity and the phenotypic features of T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, aa268-369 of the cytoplasmic domain of ZnT8, especially ZnT8-325R and ZnT8-325W, is the dominant epitope in T1D. A common non-synonymous singlenucleotide polymorphism (SNP) of SLC30A8rs13266634 (C/T polymorphism), encodes either arginine (R) by the C allele or tryptophan (W) by the T allele at aa325 of ZnT8 (14) suggests that rs13266634 SNP might be critical for humoral autoimmunity in T1D (11,15). Thus, the present study opines that SLC30A8 gene polymorphism is involved in T1D development.…”
Section: Introductionmentioning
confidence: 99%